Guidelines for integrating process safety management, environment, safety, health, and quality. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1996)
Over the years, companies have developed independent systems for managing process safety, environment, health, safety, and quality. Many aspects of these management systems are similar. Integrating EHS management systems can yield economies and improved system effectiveness. This book explains how integration reduces cost of delivery through a reduction in the number of management program steps and avoidance of redundancy; how it results in more effective programs, since the best practices can be combined into a single process; and how this integration brings a faster, and more cost effective.